Dampak Latihan Push-up Bola Bergulir dan Push-up Tubing Pada Hasil Peningkatan Daya Tahan Otot Lengan - Rustiawan, Hendra Rustiawan; Rohendi, Andang (JOSSAE (Journal of Sport Science and Education), 2021)
This study aims to find out about: (1) the effect of rolling ball push up exercises on arm to endurance (2) the effect of push up tubing exercises on to arm endurance (3) the difference between rolling ball push up exercises and push up tubing on power hold arm muscles. This research was a quasi-experimental design studied and usesd quantitative descriptive. The population used was regular students who took physical conditioning development. Totaling 70 experimental group students consisting of 35 rolling ball push-up students, and 35 push-tubing group students. The research sampling technique used subject matched ordinal pairing. The research instrument used was a 1 minute push up. The process of analyzing statistical data uses paired sample t-tests and independent sample t-tests. The results of the study proved that (1) rolling ball push up exercises significantly influenced the increased in endurance of the arm muscles by 0.93%, (2) push up tubing exercises significantly influenced the increased in endurance of the arm muscles by 0.31%. (3) there was no significant difference between rolling ball push up and push up tubing exercised on increased endurance of arm muscles.